2016
DOI: 10.4236/aim.2016.69061
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Proteins and a Possible Role for Manganese Superoxide Dismutase in Bioluminescence of <i>Panellus stipticus</i> Revealed by Suppression Subtractive Hybridization

Abstract: Suppression subtractive hybridization (SSH) was employed to investigate bioluminescence inPanellus stipticus (Bull.) P. Karst. by detecting proteins differentially expressed in bioluminescent and luminescent strains. Comparisons of luminescent and non-luminescent monokaryon cultures of North American strains revealed differences in transcript levels of proteins responsible for post-translational modification (PTM) of enzymes. A similar comparison of a luminescent strain of P. stipticus from North America with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Concerning fungi, 109 fungal taxa are known to exhibit bioluminescence all of which (except one Xylariales) are white-spored saprotrophic Basidiomycota distinguished in four phylogenetic lineages ( Chew et al, 2015 ; Ke and Tsai, 2022 ) all sharing the same type of luciferin and luciferase ( Oliveira et al, 2012 ). Interestingly, it has been shown that luminescence could be linked to the antioxidant/radical scavenging defense mechanism against some environmental stress factors ( Vydryakova and Bissett, 2016 ; Oba et al, 2017 ). Moreover, the fungal bioluminescence capacity can be used in environmental biomonitoring of metals or organic compounds and to develop toxicity tests ( Ke and Tsai, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning fungi, 109 fungal taxa are known to exhibit bioluminescence all of which (except one Xylariales) are white-spored saprotrophic Basidiomycota distinguished in four phylogenetic lineages ( Chew et al, 2015 ; Ke and Tsai, 2022 ) all sharing the same type of luciferin and luciferase ( Oliveira et al, 2012 ). Interestingly, it has been shown that luminescence could be linked to the antioxidant/radical scavenging defense mechanism against some environmental stress factors ( Vydryakova and Bissett, 2016 ; Oba et al, 2017 ). Moreover, the fungal bioluminescence capacity can be used in environmental biomonitoring of metals or organic compounds and to develop toxicity tests ( Ke and Tsai, 2022 ).…”
Section: Discussionmentioning
confidence: 99%